2008
DOI: 10.1620/tjem.214.365
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of the Trp64Arg Polymorphism of .BETA.3-Adrenergic Receptor Gene with Energy Expenditure in Response to Caffeine Among Young Healthy Women

Abstract: A close relationship between coffee intake and certain metabolic disorders is known. Caffeine, one of coffee components, can increase energy expenditure (EE), but there are considerable individual differences in the caffeine effects on EE, and the causes have not been fully established in humans. The Arg allele in the β 3 -adrenergic receptor gene (β 3 -AR), a marker for obesity-related traits, may be a contributor to individual variations in EE. This study investigated the effect of the Arg allele of β 3 -AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 20 publications
3
13
2
Order By: Relevance
“…Adverse effects of caffeine on energy deficits and weight loss were observed in many non-HIV infected populations. [51][52][53][54] In a long-term follow-up study of eighteen years, conducted in 1333 males and 4085 females with type-2 diabetes, there was a strong association between caffeine consumption (> 4 cups/day which is approximately >240 mg caffeine/day) and weight loss after controlling for age, baseline body weight, insulin and anti-diabetic drugs, physical activity and lifestyle factors. 51 Further analysis of the same study found a dose-response relationship between caffeine intake and weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Adverse effects of caffeine on energy deficits and weight loss were observed in many non-HIV infected populations. [51][52][53][54] In a long-term follow-up study of eighteen years, conducted in 1333 males and 4085 females with type-2 diabetes, there was a strong association between caffeine consumption (> 4 cups/day which is approximately >240 mg caffeine/day) and weight loss after controlling for age, baseline body weight, insulin and anti-diabetic drugs, physical activity and lifestyle factors. 51 Further analysis of the same study found a dose-response relationship between caffeine intake and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…They observed a 9-fold reduction in HIV-1 p24 antigen values in samples treated with caffeine, theobromine, paraxanthine or theophylline when compared to control solutions. 54 These analysis were controlled for confounding factors like solvents (Water vs 0.1% NaCl solution) used for different xanthine compounds, rate of growth of human peripheral mononuclear cells, differences in viral replications per unit time for different HIV-1 strains as well as the differences in reagents used for the experiment. 54 Adjustments were also made to account for variations in reverse transcriptase-polymerase chain reaction procedures (RT-PCR), southern blotting assays for HIV gag sequences, as well as the primer-probes SK38, SK39, and SK19.…”
Section: Caffeine Is Associated With Changes In Cd4 Levels As Well Asmentioning
confidence: 99%
See 3 more Smart Citations